HATE SPEECH FOR THE PURPOSE OF CREATING HOSTILITY IN INDONESIAN COMMUNITIES (Study of Criminalization and Legal Reality According to Criminal Law Experts) - Maradingin Maradingin; Pagar Pagar; Jamil Jami (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2019)
Especially printed media sheets and electronic media monitors, as well as direct educational exposure, always fulfills important information presentations that are sometimes mixed with Hate speech in the digital age, and democratization is growing very rapidly lately. In addition to its many benefits, it will also be able to threaten the integrity of the nation. Hate speech (hate speech) can trigger the occurrence; riots, hostilities, fights, even wars. This research has some influence, because the previous article "TWITTER: Expressing Hate Speech Behind Tweeting Yudha Wirawanda and Tangguh Okta Wibowo, in" Prophetic Communication Journal "Sunan Kalijaga State Islamic University, Yogyakarta, only offered findings about the pattern of tweeter usage patterns among Indonesians, where they tend to be able to freely devote their particular emotions in cyberspace. This research is specifically for questioning; How do the expressions of hate speech in Indonesia give birth to the criminalization and legal reality according to Criminal law experts? This research is presented in the form of field research. The type of research is qualitative in descriptive exposure. The sample; North Sumatra, Aceh, DKI and West Java. Research findings; "No settlement of hate speech cases is found as an act of criminalization in the midst of Indonesian society. It is estimated, there are a handful of public perceptions that criminalization of the handling of hate speech cases in Indonesia, especially the hate speech clamps aimed at the Government